ALINE: A device dedicated to understanding radio-frequency sheaths. (August 2017) - Devaux, S.; Faudot, E.; Moritz, J.; Heuraux, S.
Highlights: Sheath and presheaths around a radiofrequency are investigated by a 3D translatable Langmuir probe. 3D maps of densities and electric potential in non-magnetized plasmas show a plasma dominated by ambipolar diffusion. 3D maps of electric potential in magnetized plasmas exhibit potential wells connected to both side of the cathode. Abstract: In fusion devices, radiofrequency (RF) antennas are used for heating the plasma. Those antennas and the plasma interact with each other through the so-called RF sheaths, layers of plasma where the quasi-neutrality breaks down and large electric fields arise. Among the effects of RF sheaths, there is the enhancement of the particles and energy fluxes toward the surface of the antenna, which in turn generate hot spots and release impurities, which are both deleterious for plasma operations. RF sheaths comprehension stumbles on the difficulty to achieve in situ measurements of the sheath properties, as scrape-off layer plasmas are a harsh environment. The very goal of the ALINE device is to tackle this issue and to fulfil the blank between numerical simulations and full-scale experiment by providing measurements within the RF sheaths in a controlled environment. In this paper we report on the latest experimental results from ALINE, in which a cylindrical Langmuir probe mounted on a remotely controlled and programmable arm allows for plasma characterizations in the three dimensions of space around the stainless steel antenna, including the sheath. We present a series of density and potential profiles and three dimension (3D) maps in the plasma surrounding a stainless-steel RF antenna as well as in the sheath itself, for unmagnetized and magnetized plasmas.